Funding forms, market conditions, and dynamic effects of government R&D subsidies: evidence from China - Guo, Di; Guo, Yan; Jiang, Kun (Wiley, 2017)
We examine various factors that influence the effects of government-subsidized research and development (R&D) programs on firm productivity. Based on a panel dataset of Chinese firms, we find the effects of the Innovation Fund for Small and Medium Technology Based Firms (Innofund) are dynamic over time and are heterogeneous depending on funding forms and the level of marketization and economic development across regions. In general, Innfound has significant and positive effects on firm productivity in both the short and long run. However, the short-term effects of Innofund are stronger than the long-term ones. Additionally, the positive effects of Innofund are stronger for firms backed by interest-free bank loans than those supported by appropriation. Meanwhile, Innofund has stronger positive effects in provinces that are less market-oriented or less developed economically. Finally, the short-term effects of Innofund stay stronger than the long-term ones even after we control the funding forms and the market conditions across regions. Identification and selection concerns are addressed through the propensity score matching approach and two-stage estimation. (JEL G28 O38 H76)